Peran Pengasuh Dalam Membentuk Kedisiplinan Anak Asuh Di Panti Asuhan Hayat Sabungan Jae - Nasution, Mulia (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2022)
This study aims to find out what media are used by caregivers in shaping the discipline of foster children at the Hayat Sabungan Jae Orphanage. And how do caregivers shape the disciplinary activities of foster children at the Hayat Sabungan Jae Orphanage. This research is a qualitative research using descriptive method. Data collection techniques in this study are: observation, interviews, and document study. The technique of guaranteeing the validity of the data is the extension of participation, persistence of observation. Management techniques and conclusion. The research results obtained are that the role of caregivers in shaping the discipline of foster children is as a motivator, assisting in developing and physical growth, assisting and developing emotional growth, as a builder of social attitudes, as an educator and as a coach. The role of caregivers in shaping the discipline of foster children is said to be quite active, this can be seen from the efforts to shape and habituate the caregivers and of course it all starts with the caregivers themselves who are role models for foster children